Knocking down GALNT6 promotes pyroptosis of pancreatic ductal adenocarcinoma cells through NF-κB/NLRP3/GSDMD and GSDME signaling pathway - Ding, Mengyang; Liu, Jingyu; Lv, Honghui; Zhu, Yanlin; Chen, Yumiao; Peng, Hui; Fan, Sairong; Chen, Xiaoming (Frontiers in Oncology, 2023)
Pancreatic ductal adenocarcinoma (PDAC) is the most lethal malignancy. Polypeptide N-acetylgalactosaminyl transferase-6 (GALNT6) is frequently overexpressed in PDAC. However, the role of GALNT6 in the PDAC remains unclear. In this study, we found that the expression of GALNT6 was associated with advanced tumor stage, and had an AUC value of 0.919 in pancreatic cancer based on TCGA dataset. Knockdown of GALNT6 inhibited cell proliferation, migration, invasion and cell cycle arrest of PDAC cells. Meanwhile, knockdown of GALNT6 increased the expression levels of inflammatory factors, including IL-1β, IL-6, TNF-α and IL-18, and promoted the release of inflammasome, which enhanced the pyroptosis of PDAC cells, as evidenced by an increasing of GSDMD and GSDME in PDAC cells.GALNT6 suppressed the expression of NLRP3 and GSDMD by glycosylation of NFκB P65 and inhibiting the nucleus localization of NFκB P65.Additionally, GALNT6 promotes the degradation of GSDME by O-glycosylation. These results suggested that GALNT6 regulates the pyroptosis of PDAC cells through NFκB P65/NLRP3/GSDMD and GSDME signaling, and provides novel insights into the roles of GALNT6 in PDAC progression.